Aquaculture economic analysis : - Yung, C. Shang (World Aquaculture Society, 1990)
This book give students an idea of aquaculture economics. Examples of economic solutions to common problems help you understand the need for economic application to aquaculture and the success that may come with sound economic planning and management. It also provides coverage of virtually all basic principles of microeconomics, farm management finance, and marketing applicable to the aquacultural industry.